2017
DOI: 10.1097/hcr.0000000000000231
|View full text |Cite
|
Sign up to set email alerts
|

Directly Measured Physical Function in Cardiac Rehabilitation

Abstract: Purpose The Short Physical Performance Battery (SPPB) is a strong predictor for risk of physical disability in older adults. Roughly half of individuals participating in phase II cardiac rehabilitation (CR) are ≥65 years of age, many presenting with low aerobic capacities and may be at increased risk for physical disability. Methods The cohort consisted of 196 consecutive patients (136 males), aged ≥65 years, entering CR were prospectively assessed by SPPB. Data were also obtained for age, self-reported phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…However, in frail older adults patients (SPPB score ≤ 8) who participated in exercise-based CR (involving resistance, flexibility, balance exercise) after surgery, Molino-Lova et al [ 14 ] demonstrated significant improvements in SPPB score compared to CG one year after discharge from CR. Furthermore, results from Rengo et al [ 15 ] show patients who were admitted to CR with SPPB score ≤ 8 as experiencing significantly more pronounced improvement in gait speed and leg strength (chair-stand) compared to the overall CR population as a result of participation in combined aerobic/resistance training. Moreover, high-speed resistance exercise participation training for older adults living in a community demonstrably improves their SPPB score [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in frail older adults patients (SPPB score ≤ 8) who participated in exercise-based CR (involving resistance, flexibility, balance exercise) after surgery, Molino-Lova et al [ 14 ] demonstrated significant improvements in SPPB score compared to CG one year after discharge from CR. Furthermore, results from Rengo et al [ 15 ] show patients who were admitted to CR with SPPB score ≤ 8 as experiencing significantly more pronounced improvement in gait speed and leg strength (chair-stand) compared to the overall CR population as a result of participation in combined aerobic/resistance training. Moreover, high-speed resistance exercise participation training for older adults living in a community demonstrably improves their SPPB score [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This trend was observed at all three time points in our study. This could be explained by the concerns regarding SPPB score and its ceiling effect for individuals with higher fitness levels [ 10 , 15 , 38 ]. In our study, the physical frailty level improved in both groups during the observation period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical activity levels are generally low among even high-functioning stroke survivors, potentially contributing to further declines in physical function [34]. For heart disease, exercise-based cardiac rehabilitation is beneficial for improving fitness and health [35], and improvements in physical function have also been noted [36]. We do not have information in the current study as to whether participants who reported a stroke or heart disease were in cardiac rehabilitation, and therefore cannot determine if our results are reflective of patients who completed these programs.…”
Section: Discussionmentioning
confidence: 99%